2007
DOI: 10.1002/jbm.a.31658
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin is a critical protein adhesion substrate for IL‐4‐induced foreign body giant cell formation

Abstract: An in vitro system of interleukin (IL)-4-induced foreign body giant cell (FBGC) formation was utilized to define the adhesion protein substrate(s) that promotes this aspect of the foreign body reaction on biomedical polymers. Human monocytes were cultured on cell culture polystyrene surfaces that had been pre-adsorbed with a synthetic arginine-glycine-aspartate (RGD) peptide previously found to support optimal FBGC formation, or with various concentrations of potential physiological protein substrates, i.e. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 42 publications
(107 reference statements)
5
83
0
6
Order By: Relevance
“…46 McNally et al observed lower monocyte/macrophage adhesion and no IL-4-induced FBGC formation on standard cell culture polystyrene preadsorbed with Fg when compared with RGD-coated substrates at all time points studied (0, 3 and 7 days). 37 On the other hand, others have found enhanced macrophage adhesion on different surfaces preadsorbed with Fg, relative to corresponding uncoated surfaces, 2 h and 1 day after cell seeding. 47 In addition, Yun et al showed that Fg preadsorbed onto poly(tetrafluoroethylene/ hexafluoropropylene) (FEP) copolymers induced higher monocyte adhesion on surfaces containing carboxyl groups compared with an FEP surface with only amine groups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…46 McNally et al observed lower monocyte/macrophage adhesion and no IL-4-induced FBGC formation on standard cell culture polystyrene preadsorbed with Fg when compared with RGD-coated substrates at all time points studied (0, 3 and 7 days). 37 On the other hand, others have found enhanced macrophage adhesion on different surfaces preadsorbed with Fg, relative to corresponding uncoated surfaces, 2 h and 1 day after cell seeding. 47 In addition, Yun et al showed that Fg preadsorbed onto poly(tetrafluoroethylene/ hexafluoropropylene) (FEP) copolymers induced higher monocyte adhesion on surfaces containing carboxyl groups compared with an FEP surface with only amine groups.…”
Section: Discussionmentioning
confidence: 95%
“…RGD was used as a positive control surface for macrophage development and adhesion and FBGC formation, as previously reported. [37][38][39] Adsorbed RGD is widely recognized for its adhesion-promoting capabilities in that it presents multiple copies of the RGD (arginine-glycine-aspartate) cell attachment sequence to integrin receptors, thus facilitating their engagement.…”
Section: Adsorption Of Human Fg and Rgd Peptidementioning
confidence: 99%
“…Индуци-рованное IL-4 образование ГКИТ в условиях in vitro характеризуется экспрессией αM/β2, αX/β2, α5/β1, α2/β1 и α3/β1, что указывает на роль взаи-модействий фрагментов комплемента С3b, фиб-рина, фибриногена, фибронектина, фактора X и витронектина в местах имплантации биоматериа-лов. В процессе IL-4 зависимого формирования ГКИТ определена последовательность активности α-интегринов, которая, по данным Mc Nally et al, [42] следующая: αMβ2, αXβ2, α5β1> αVβ1> α3β1 и α2β1. В качестве лигандов ранней адгезии с β2 интегринами идентифицированы комплемент и фибриноген [42].…”
unclassified
“…В процессе IL-4 зависимого формирования ГКИТ определена последовательность активности α-интегринов, которая, по данным Mc Nally et al, [42] следующая: αMβ2, αXβ2, α5β1> αVβ1> α3β1 и α2β1. В качестве лигандов ранней адгезии с β2 интегринами идентифицированы комплемент и фибриноген [42].…”
unclassified
See 1 more Smart Citation